Analysis Efectivity and Eficiency Financial Management Performance of Regional Revenue Agency - Jaa, Anasthasya; Susilowati, Dwi; Moorcy, Nadi Hernadi (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of this study is to determine the level of effectiveness and efficiency and performance of regional financial management from 2021 to 2023 in East Kutai Regency. This study applies a quantitative descriptive approach with the aim of assessing the level of effectiveness, efficiency, and performance of regional financial management at the East Kutai Regency Regional Revenue Agency. The data analyzed are in the form of Budget Realization Reports (LRA) from 2021 to 2023, using descriptive statistical analysis techniques through the calculation of effectiveness and efficiency ratios based on the provisions of Law Number 33 of 2004.